Significant haematological alterations in clozapine-treated patients: prevalence and clinical correlation - Tabara, Muhammed Fatih; Akar, Cafer Baris; Atdagi, Mehmet Kadir; Gurok, Mehmet Gurkan; Atmaca, Murad (Cambridge Univ Press, 2024)
Objectives: Clozapine is an atypical antipsychotic crucial for treatment-resistant schizophrenia, characterised by its multi-receptor targeting, including serotonin (5-HT2A, 5-HT2C) and dopamine (D1, D2, D3, D4) receptors, among others. This broad mechanism is effective against positive symptoms of schizophrenia with a lower incidence of extrapyramidal side effects. However, clozapine poses significant haematological risks, notably agranulocytosis, necessitating stringent blood monitoring protocols. Methods: This study examined haematological parameters in 157 patients on clozapine therapy, analysing the prevalence and clinical correlations of haematological abnormalities such as leucocytosis, thrombocytosis, and alterations in red blood cell distribution width (RDW) and mean platelet volume (MPV). Results: The findings revealed leucocytosis in 36.9% of patients, thrombocytosis in 8.9%, and elevated RDW in 23.6%. Notably, higher clozapine doses were associated with leucocytosis, though no significant correlations were found between clozapine dose, duration of use, and changes in RDW, mean corpuscular haemoglobin concentration, or MPV. Conclusion: The study's results underscore the necessity of regular haematological monitoring to mitigate the risks of clozapine therapy while leveraging its therapeutic benefits. Additionally, the study suggests personalised dosing strategies to balance efficacy and safety, particularly in managing clozapine-induced haematological changes.
Keywords: Clozapine; haematological adverse effects; leucocytosis; red blood cell distribution width; mean platelet volume; mean corpuscular haemoglobin concentration